A Note to Schooling in Development Accounting - Francesco Caselli; Antonio Ciccone (Asian Development Bank (ADB), 2012)
How much would output increase if underdeveloped economies were to increase their levels of schooling? We contribute to the development accounting literature by describing a non-parametric upper bound on the increase in output that can be generated by more levels of schooling. The advantage of our approach is that the upper bound is valid for any number of schooling levels with arbitrary patterns of substitution/complementarity. We also quantify the upper bound for all economies with the necessary data, compare our results with the standard development accounting approach, and provide an update on the results using the standard approach for a large sample of countries.
hdl:11540/1273
Keywords: 330; Development; Bildungsinvestition; Schule; Öffentliche Ausgaben; Wirtschaftswachstum; Entwicklungsländer